Assessment of beam‐matched linacs quality/accuracy for interchanging SBRT or SRT patient using VMAT without replanning. Issue 1 (7th November 2018) - Xu, Zhengzheng; Warrell, Gregory; Lee, Soyoung; Colussi, Valdir; Zheng, Yiran; Ellis, Rodney; Machtay, Mitchell; Podder, Tarun
Abstract: Purpose: Dosimetric accuracy is critical when switching a patient treated with stereotactic body radiation therapy (SBRT) or stereotactic fractionated radiotherapy (SRT) among beam‐matched linacs. In this study, the dose delivery accuracy of volumetric modulated arc therapy (VMAT) plans for SBRT/SRT patients were evaluated on three beam‐matched linacs. Method: Beam data measurements such as percentage depth dose (PDD10 ), beam profiles, output factors, and multi‐leaf collimator (MLC) leaf transmission factor for 6 MV photon beam were performed on three beam‐matched linacs. The Edge™ diode detector was used for measurements of beams of field size less than 5 × 5 cm 2 . Ten lung and 15 brain plans were generated using VMAT with the same beam model. Modulation complexity score of the VMAT plan (MCSv) was used as a plan complexity indicator. Doses were measured using ArcCHECK™ and GafChromic™ EBT3 films. The measurements were compared with calculated doses through absolute dose gamma comparison using 3%/2 mm and 2%/2 mm criteria. Correlation between difference in passing rates among beam‐matched linacs and MCSv was evaluated using the Pearson coefficient. Point doses were measured with the A1SL micro ion chamber. Results: Difference in beam outputs, beam profiles, and MLC leaf transmission factors of beam‐matched linacs were all within ±1%, except the difference in output factor for 1 × 1 cm 2 field between linac 1 and 3 (1.3%). For all 25 cases, passing rates of measured doses on three linacs were all higher than 90% when using 2%/2 mm gamma criteria. The average difference in point dose measurements among three beam‐matched linacs was 0.1 ± 0.2% ( P  > 0.05, one‐way ANOVA). Conclusion: Minimal differences in beam parameters, point doses, and passing rates among three linacs proved the viability of swapping SBRT/SRT using VMAT among beam‐matched linacs. The effect of plan complexity on passing rate difference among beam‐matched linacs is not statistically significant.